PROBLEMS IN THE IMPLEMENTATION OF CARBON TAXES AS AN INSTRUMENT TO PROMOTE A SUSTAINABLE ECONOMY IN INDONESIA: PROBLEMATIKA PENERAPAN PAJAK KARBON SEBAGAI INSTRUMEN PENDORONG EKONOMI BERKELANJUTAN DI INDONESIA - Sutedjo, Arya Anasta Adam (Constitutional Law Society, 2025)
This study discusses the problems of implementing carbon tax as an instrument for reducing greenhouse gas emissions and promoting sustainable economy in Indonesia. The carbon tax, which is regulated in Law No. 7 of 2021 and Government Regulation No. 50 of 2022, aims to minimize carbon emissions from the electricity, transportation, and manufacturing industries. However, its implementation has significant socioeconomic impacts, including increased production costs, higher prices, and pressure on people's purchasing power, especially among the lower-middle class. A normative analysis was conducted using a statute approach, a conceptual approach, and a comparative approach by examining the practices of other countries, such as Sweden, which has successfully integrated carbon tax with fiscal incentives, and Australia, which has demonstrated the negative risks of carbon tax without social compensation. The results of the study show that the unilateral implementation of carbon taxes can threaten public welfare and economic stability, thus requiring an ideal mechanism based on the principles of sustainable economics. This mechanism includes providing fiscal incentives, developing renewable energy such as geothermal, biomass, and solar energy, and implementing transparent and effective carbon trading, including cap and trade and emission offset systems. With this strategy, carbon emissions can be reduced effectively without sacrificing economic growth and social welfare. These findings emphasize the need for inclusive, adaptive carbon tax policies that are integrated with economic incentives, clean technology, and multi-stakeholder participation as a model for sustainable environmental management.